Evaluation of the conceptual model on shrubbyness-desertification on arid rangelands - Torres, Y. A. (2018)
Advancement of shrubbyness (increase in plant cover and density of woody species) on different environments world-wide has generated an increasing interest in the scientific community, particularly because of its association with the desertification process which is increasing, also at a world-wide level. There are two opposing positions, both of them validated by scientific evidences. The greatly accepted position recognizes shrubbyness as one of themechanisms conducing to desertification in natural environments, cataloguing it as a negative process. A different view, based on recent studies, suggests that shrubbyness should be considered as a positive process because it will drive to a reversal of desertification, depending on the environment and the study species. This review is presented within this framework. It reviews the existent relationship between shrubbyness and desertification, and proposes an approach that should be considered in future research.